2023
DOI: 10.3390/su15075735
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship between Cultural Intelligence (CQ) and Management Competencies (MC)

Abstract: The aim of this study is to demonstrate the importance of Cultural Intelligence (CQ) in management performance through measurable performance assessment. In an empirical study, “Cultural Intelligence and Management Competencies”, managers provided a self-assessment and their subordinates also reported on their performance. Correlation analysis of the results of this study was used to examine the relationship between managers’ CQ and their Management Competencies. Among the factors examined (CQ, gender, origin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
(58 reference statements)
0
0
0
Order By: Relevance
“…Research on managers has also shown that female managers' social sensitivity, flexibility, resilience, and motivational levels are higher than those of the male managers (Garamvölgyi and Rudnák 2023). Research conducted on male and female ministers demonstrated systematic differences between women and men in the practice of the pastoral vocation, which corresponds with the differences in secular working attitudes.…”
Section: Differences In Male and Female Conceptions Of Calling Career...mentioning
confidence: 99%
“…Research on managers has also shown that female managers' social sensitivity, flexibility, resilience, and motivational levels are higher than those of the male managers (Garamvölgyi and Rudnák 2023). Research conducted on male and female ministers demonstrated systematic differences between women and men in the practice of the pastoral vocation, which corresponds with the differences in secular working attitudes.…”
Section: Differences In Male and Female Conceptions Of Calling Career...mentioning
confidence: 99%
“…Korábbi kutatásunk eredményei tulajdonképpen alátámasztják a diákok által megélt külföldi tapasztalat pozitív hatását a CQ-értékek alakulására, de természetesen a munkavállalói felnőtt felmérés eredményeiben sokkal markánsabb értékek jelennek meg: a Viselkedési CQ-értékek kivételével mindegyik kategóriában szignifikáns különbség mutatkozott a multikulturális tapasztalatot átéltek előnyére (Garamvölgyi & Rudnák, 2023). Továbbá az is "beszédes" adat, hogy amíg a középiskolások 6,5%-ának volt hosszútávú külföldi tapasztalata, a munkavállalóknál ez 57% volt, a hosszú-és rövidtávú külföldi tapasztalok együttesen a középiskolások 20%-át, a felnőtt munkavállaóknak pedig 75%-át jelenti.…”
Section: Forrás: Saját Szerkesztésunclassified